PROTOTYPE SMART JACKET UNTUK DRIVER OJEK ONLINE BERBASIS INTERNET OF THINGS (IOT) DI KOTA SURABAYA - Adi Winarno; Ilham, Mohamad; Muhamad Anang Sucipto (Universitas PGRI Adi Buana Surabaya, 2024)
The research aims to design an automatic cooling jacket based on the Internet of Things (smart jacket) that can be used when riding motorbikes, including online motorcycle taxis. The methods used in this research include user needs analysis, system design, prototypes, and fan speed performance testing. In the user needs analysis stage, a survey was conducted among motorcyclists to identify problems faced when riding in hot weather conditions. Next, a system design consisting of a temperature sensor and an IoT communication module was carried out. After designing the system, an automatic cooling jacket prototype was developed. This prototype is equipped with a temperature sensor that will detect the rider's body temperature level, and an IoT communication module to allow users to control the jacket via an application on a smartphone. The results of this research show that an IoT-based automatic cooling jacket can effectively reduce the body temperature of motorcyclists when riding in hot weather. In speed performance testing, this jacket succeeded in reducing the rider's body temperature efficiently. This research is expected to contribute to the development of wearable technology that can increase comfort and safety for motorcyclists. Apart from that, this research can also be the basis for developing IoT-based automatic cooling jacket products that can be mass-produced and sold on the market.